Ngôn ngữ hình tượng trong lời bài hát tiếng Anh và đề xuất một số hoạt động để thu hút người học: Trường hợp album The Tortured Poets Department của Taylor Swift - Hà Thị Vũ Hà , Hà Thị Vũ Hà (Tạp chí Giáo dục, 2026)
The growing recognition of incorporating figurative language into English literacy highlights its importance in enhancing students’ understanding of nuanced meanings and cultural contexts. As educational practices evolve, there is a greater emphasis on using figurative language to deepen students’ engagement with texts and improve their interpretative skills. This research aims to examine figurative language in Taylor Swift’s album “The Tortured Poets Department” to explore how figurative devices in the album, especially metaphors, enrich the poetic messages by weaving intricate layers of meaning, elevating emotions, and creating vivid imagery that resonates deeply with listeners. With the use of qualitative analysis of song lyrics, the results showed that incorporating these figurative devices, particularly metaphors, into English lessons can greatly improve students’ cultural awareness, engagement, and overall learning experience. These findings were used to suggest practical classroom activities that make language learning more interactive and effective, demonstrating how contemporary music can enrich English education through real-world examples.